Perkembangan Pasar Tradisonal dan Keberadaan Pasar Modern di Kota Palembang - Rita Martini; Sabrina Sabatiny (Politeknik Negeri Sriwijaya, 2018)
This study are to give information to the public regarding the development of traditional markets in the city of Palembang. For Trading Company (PD) Market Palembang Jaya, are expected to contribute towards the implementation of preventive measures that must be done to maintain the existence of traditional markets and increasing contribution to economic development in Palembang. Data was collected by distributing questionnaires about the development of traditional markets in Palembang on the traditional market revenue. The results showed that the development of traditional markets was increased, although followed by the growth of modern markets in Palembang.